2014
DOI: 10.5539/gjhs.v7n1p161
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health Risks Among Trichloroethylene-Exposed Workers in a Clock Manufacturing Factory

Abstract: Trichloroethylene (TCE) is an important volatile organic compound once widely used in industry throughout the world. Occupational exposure to TCE can cause a number of health hazards such as allergic reactions and genetic damage. The purpose of this study was to evaluate occupational exposure to TCE, by analysis of the air in the breathing zone and of urine from workers employed in a clock manufacturing factory. A subjective symptom survey was conducted by using a self-administered questionnaire to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
2
6
0
Order By: Relevance
“…20 In our study, mean urinary TCA levels of workers who were exposed to TCA (20.5 mg/L) were significantly higher than the control subjects (5 mg/L). The mean urinary TCA levels in this study was lower than that reported by Cheng et al 21 but was similar to that reported by Singthong et al 22…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…20 In our study, mean urinary TCA levels of workers who were exposed to TCA (20.5 mg/L) were significantly higher than the control subjects (5 mg/L). The mean urinary TCA levels in this study was lower than that reported by Cheng et al 21 but was similar to that reported by Singthong et al 22…”
Section: Discussionsupporting
confidence: 89%
“…20 In our study, mean urinary TCA levels of workers who were exposed to TCA (20.5 mg/L) were significantly higher than the control subjects (5 mg/L). The mean urinary TCA levels in this study was lower than that reported by Cheng et al 21 but was similar to that reported by Singthong et al 22 The mechanism underlying the toxicity of TCE is diverse and not definitely understood yet. As it was reported by previous studies, exposure to volatile organic solvents induced oxidative stress in animal and cell line studies.…”
Section: Discussionsupporting
confidence: 87%
“…No association was seen between solvent exposure and lung function parameters in both studies. In another study of 244 workers in a clock manufacturing factory in Bangkok (Thailand), associations between TCE exposure and various health outcomes including skin, respiratory and allergy symptoms were evaluated by self-administered questionnaire [60]. Workers were classified as exposed to TCE or non-exposed based on their type of job.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…some diseases, particularly liver disorders (12). Researchers showed that inhalation exposure to TCE can produce several forms of liver disease such as fatty liver, cirrhosis, hepatic necrosis (13) and hematological disorders (14). Animal exposure to TCE using a specific mouse model of systemic autoimmunity induced an autoimmune hepatitis-like syndrome (15).…”
Section: Discussionmentioning
confidence: 99%